2017
DOI: 10.1136/bmjopen-2017-018105
|View full text |Cite
|
Sign up to set email alerts
|

Post-operative patient-related risk factors for chronic pain after total knee replacement: a systematic review

Abstract: ObjectiveTo identify postoperative patient-related risk factors for chronic pain after total knee replacement (TKR).DesignThe systematic review protocol was registered on the International Prospective Register of Systematic Reviews (CRD42016041374). MEDLINE, Embase and PsycINFO were searched from inception to October 2016 with no language restrictions. Key articles were also tracked in the Institute for Scientific Information (ISI) Web of Science. Cohort studies evaluating the association between patient-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 54 publications
2
74
0
4
Order By: Relevance
“… 62 Post-surgical factors may be risk factors for chronic pain through limiting rehabilitation and recovery; however, a systematic review has found that there is insufficient evidence to draw firm conclusions about the association between postoperative factors and chronic pain after TKA. 80 Although acute postoperative pain is often assumed to be associated with chronic pain, and is a strong risk factor for other surgical populations, 6 there is little evidence to support this association in patients with TKA after controlling for preoperative pain severity. 56 , 81 However, ongoing work to understand the transition of acute postoperative pain to chronic pain in a surgical setting may help to inform strategies to minimize suboptimal pain outcomes after TKA.…”
Section: Risk Factorsmentioning
confidence: 99%
“… 62 Post-surgical factors may be risk factors for chronic pain through limiting rehabilitation and recovery; however, a systematic review has found that there is insufficient evidence to draw firm conclusions about the association between postoperative factors and chronic pain after TKA. 80 Although acute postoperative pain is often assumed to be associated with chronic pain, and is a strong risk factor for other surgical populations, 6 there is little evidence to support this association in patients with TKA after controlling for preoperative pain severity. 56 , 81 However, ongoing work to understand the transition of acute postoperative pain to chronic pain in a surgical setting may help to inform strategies to minimize suboptimal pain outcomes after TKA.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Mechanical explanations include altered gait, prosthesis loosening and effects on ligaments 14 15. Psychological factors including depression and catastrophising may also influence outcomes 16–19. Much research has focused on preoperative predictors of outcomes and these include pain intensity, presence of widespread pain, anxiety, depression and catastrophising 10 20.…”
Section: Introductionmentioning
confidence: 99%
“…However, identifying high risk patients is challenging; preoperative models to identify patients at risk of a poor outcome have low predictive power, 36 37 and the evidence for postoperative risk factors is limited. 47 However, research is currently ongoing to evaluate whether providing a rehabilitation programme for patients at risk of a poor outcome 34 or are ‘functioning poorly’ at 6 weeks after TKR 35 can improve longer-term outcomes.…”
Section: Discussionmentioning
confidence: 99%